2018
DOI: 10.1101/331066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral health-related quality of life in elderly women participating in a coexistence group in southern Brazil: Oral health and quality of life in elderly women

Abstract: Oral health-related quality of life in elderly women participating in a 5 coexistence group in southern Brazil 6 7 8 Oral health and quality of life in elderly women Abstract 25 The objective of this work was to evaluate the association between 26 quality of life with the oral health in elderly women participating in a coexistence 27 group in Southern Brazil. Study of the descriptive type, analytical, cross-28 sectional approach, with women aged 60 years or more, participants of a 29 coexistence group in a cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The similar results were obtained by Saxena et al [ 42 ] who found no significant differences between men and women in individual OHIP -14 domains. Dallasta et al [ 43 ] who studied women aged 60 and more, recorded the highest values for "physical pain" = 1.98±1.41, "psychological distress" = 1.83±1.92 and "physical disability" = 1.63±1.53.…”
Section: Discussionmentioning
confidence: 99%
“…The similar results were obtained by Saxena et al [ 42 ] who found no significant differences between men and women in individual OHIP -14 domains. Dallasta et al [ 43 ] who studied women aged 60 and more, recorded the highest values for "physical pain" = 1.98±1.41, "psychological distress" = 1.83±1.92 and "physical disability" = 1.63±1.53.…”
Section: Discussionmentioning
confidence: 99%
“…The similar results were obtained by Saxena et al [41] who found no signi cant differences between men and women in individual OHIP − 14 domains. Dallasta et al [42] who studied women aged 60 and more, recorded the highest values for "physical pain" = 1.98 ± 1.41, "psychological distress" = 1.83 ± 1.92 and "physical disability" = 1.63 ± 1.53.…”
Section: Discussionmentioning
confidence: 98%